The Effectiveness of Recognizing the Existence of Traditional Institutions in Indonesia Based on The Constitution - Asfia, Hilyatul; Wijaya, Andika; D. Bangas, Karlinae; Milionhart, Benaya (Advances In Social Humanities Research, 2024)
Plurality is a social fact that cannot be avoided in Indonesia. The diversity of Indonesian people's tribes, religions, races, languages ??and religions shows their diversity. The founders of the Republic of Indonesia used the basic philosophy of "unity in diversity" to show the diverse social reality of the Indonesian nation, and the basic philosophy of "tunggal ika" to show the desire to unite the entire Indonesian nation into one. With the combination of the two, the philosophical motto of the Indonesian nation is "Unity in Diversity", which means unity in diversity. Apart from various different societal systems and structures, this community has unique norms that are considered customs and are adhered to by its community members. Customary law communities are genealogical or territorial communities that are prosperous and have citizens who are different from members of other legal communities and can act as independent and independent legal subjects. One of the problems in administering customary law communities is the existence of customary institutions. The problem currently occurring is that there is no clear and integrated mechanism for recognition and protection procedures. Regulations regarding procedural mechanisms for recognizing the rights of customary law communities through sectoral legislation are often not adhered to by various parties, in fact the nature of the regulations which do not focus on specifically regulating customary law community institutions has an impact on ineffective implementation even though customary institutions have relevance to the Indonesian constitution. The existing mechanism only concerns the process of identification, verification and determining its existence, which makes it increasingly pressured by development activities that do not pay attention to traditional rights and threaten local wisdom.